2002
DOI: 10.1097/00006534-200207000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Denervation Increases Satellite Cell Susceptibility to Apoptosis

Abstract: Peripheral motor nerve trauma severely compromises skeletal muscle contractile function. Satellite cells respond to denervation by dividing multiple times, ultimately fusing with other satellite cells or myocytes to form new muscle fibers. After chronic denervation, satellite cell numbers decline dramatically, impairing the ability to regenerate and repair myofibers. This satellite cell depletion may contribute to the mechanical deficit observed in denervated or reinnervated muscle. Apoptosis, an evolutionaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 35 publications
8
69
1
Order By: Relevance
“…Therefore, it is suggested that the mechanical load applied to the central region of fibers may be very low or zero even after 16 days of unloading. This view is consistent with the report of Jejurikar et al (2002), who reported that chronic denervation of soleus and gastrocnemius muscles of rats increased the susceptibility of satellite cells to apoptosis. Combined, these data suggest that the suicide-related pathways for the removal of satellite cells may be induced in response to chronic unloading.…”
Section: Satellite Cellssupporting
confidence: 93%
“…Therefore, it is suggested that the mechanical load applied to the central region of fibers may be very low or zero even after 16 days of unloading. This view is consistent with the report of Jejurikar et al (2002), who reported that chronic denervation of soleus and gastrocnemius muscles of rats increased the susceptibility of satellite cells to apoptosis. Combined, these data suggest that the suicide-related pathways for the removal of satellite cells may be induced in response to chronic unloading.…”
Section: Satellite Cellssupporting
confidence: 93%
“…This implies that long-term denervation may cause satellite cells to lose their capability to enter the mitotic cell cycle (282). Second, satellite cells from muscle denervated for 6 and 10 wk displayed a twofold increase of apoptosis, compared with control cells from normal innervated muscle (248). Although the underlying mechanism of a neural influence on satellite cell behavior is still elusive, neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are involved.…”
Section: Local Milieumentioning
confidence: 99%
“…However, satellite cells do not seem to be involved in muscle hypertrophy mediated by this pathway (Amthor et al 2009). In rodent models of unloading-induced muscle atrophy, satellite cells initially become activated (Ferreira et al 2006), but eventually decrease in number (Schultz et al 1994;Mozdziak et al 2000;Hawke and Garry 2001;Jejurikar et al 2002;Jejurikar and Kuzon 2003), and those that remain are dysfunctional (Mitchell and Pavlath 2004). These studies have implications not only for repair and maintenance of skeletal muscle during periods of immobilization but also for using satellite cells to repair muscle that is already affected by disuse atrophy as, for example, in muscular dystrophies.…”
Section: Satellite Cell Response To Exercise and Contribution To Skelmentioning
confidence: 99%